Pembelajaran Qiraat di Era Digital: Telaah Maqra’ah Qur’aniyyah Online - Himmad, Gumaa Ahmed; Mokhtar, Ahmad Baha' Bin; Hidayatil, Rifqi (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2024)
Maqra’ah, traditionally, has served as a cornerstone for Quranic education, aimed at preserving and transmitting the teachings of the Quran across generations within the Islamic community. Initially centered on face-to-face interactions, Maqra’ah has experienced a paradigm shift with the advent of modern technology, manifesting in the form of online Maqra’ah. This innovative model breaks down geographical and temporal barriers, connecting teachers and students globally. Despite its significant potential, this study identifies that the adoption of online Maqra’ah, especially those focused on Qiraat learning, remains relatively underexplored. Consequently, this research aims to describe various online Maqra’ah platforms offering Qiraat learning programs, utilizing a literature study method. The findings reveal a diversity of Quranic Maqra’ah offering Qiraat education programs in contemporary times. The emergence of online Maqra’ah serves as an effective step in preserving the knowledge of Qiraat, which has become somewhat alienated among the Muslim community in recent decades. The advent of online Maqra’ah presents a new alternative, facilitating students in deepening their Qiraat studies and potentially serving as an effective and flexible learning method..Abstract: Maqra’ah, secara tradisional, merupakan pusat pembelajaran Al-Quran yang bertujuan untuk mempertahankan dan menyampaikan pengajaran Al-Quran dari generasi ke generasi dalam komunitas Islam. Maqra’ah yang pada awalnya berfokus pada interaksi tatap muka, telah mengalami pergeseran dengan pemanfaatan teknologi modern yang berupa maqra’ah online. Model inovatif ini memecahkan batasan geografis dan waktu, menghubungkan guru dan murid dalam lingkup global. Meskipun potensinya yang besar, penelitian ini mengidentifikasi bahwa adopsi maqra’ah online, khususnya yang fokus pada pembelajaran ilmu qiraat, masih belum begitu populer. Oleh karena itu kajian ini bertujuan untuk mendeskripsikan berbagai platform maqra’ah online yang menyediakan pembelajaran ilmu qiraat dengan metode studi kepustakaan. Hasil kajian ini menunjukkan bahwa terdapat berbagai macam maqra’ah Al-Quran yang menawarkan program pembelajaran ilmu qiraat di zaman sekarang. Munculnya maqra’ah online telah menjadi sebagai satu langkah efektif dalam melestarikan ilmu qiraat yang sudah terasa asing dalam kalangan umat Islam sejak beberapa dekade terakhir. Kehadiran maqra’ah online telah menjadi alternatif baru yang dapat memudahkan para pelajar mendalami studi qiraat dan berpotensi menjadi metode pembelajaran yang efektif dan fleksibel.